Agromyces tropicus sp. nov., isolated from soil - Chitti Thawai; Somboon Tanasupawat; Khanit Suwanborirux; Takuji Kudo (My University, 2010)
Two actinomycete strains, CM9-9(T) and AK2-48, which produced straight rod-shaped, non-motile cells, were isolated from soils in Chiang Mai and Phuket provinces, respectively, Thailand. The morphological and chemotaxonomic characteristics of the isolates coincided with those of the genus Agromyces. Phylogenetic analysis using 16S rRNA gene sequences also indicated that the isolates were clearly separated from their closest relative, Agromyces aurantiacus YIM 21741(T), and should be classified in the genus Agromyces. Furthermore, a combination of DNA-DNA hybridization results and physiological and biochemical properties indicated that the isolates could be distinguished from all recognized members of the genus Agromyces. The isolates therefore represent a novel species, for which the name Agromyces tropicus sp. nov. is proposed. The type strain is CM9-9(T) (=JCM 15672(T) =BCC 34764(T)).
Keywords: Genomics and Phylogenetic Studies